PENGARUH FASILITAS, PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA KUNTI N AZIZAH MAKE UP DI SITUBONDO - Aluf, Wilda Al; Subaida, Ida; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2025)
In an ever-evolving and increasingly competitive industrial world, marketing management plays a strategic role in managing and enhancing business success, including in the beauty service sector such as Make-Up Artists. This intense competition is expected to motivate business actors to quickly adapt to the dynamics of the business environment in order to meet consumer needs, desires, and expectations. This study aims to analyze and examine the influence of Facilities, Promotion, and Service Quality on Purchase Decisions with Customer Satisfaction as an intervening variable at Kunti N Azizah Make Up in Situbondo. The sampling technique used in this study was purposive sampling. Data analysis and hypothesis testing were carried out using the Structural Equation Modeling – Partial Least Square (PLS-SEM) approach. The results of the direct effect hypothesis testing using Smart PLS 3.0 application showed that Facilities have a significant positive effect on Customer Satisfaction, Promotion has a positive but not significant effect on Customer Satisfaction, Service Quality has a significant positive effect on Customer Satisfaction, Facilities have a positive but not significant effect on Purchase Decisions, Promotion has a positive but not significant effect on Purchase Decisions, Service Quality has a significant positive effect on Purchase Decisions, and Customer Satisfaction has a significant positive effect on Purchase Decisions. The results of the indirect effect hypothesis testing indicate that Facilities have a positive but not significant effect on Purchase Decisions through Customer Satisfaction, Promotion has a positive but not significant effect on Purchase Decisions through Customer Satisfaction, and Service Quality has a significant positive effect on Purchase Decisions through Customer Satisfaction.